2001
DOI: 10.1093/molehr/7.4.373
|View full text |Cite
|
Sign up to set email alerts
|

The HLA-G genotype is potentially associated with idiopathic recurrent spontaneous abortion

Abstract: The causes for recurrent spontaneous abortion (RSA) remain unknown in a large proportion of the cases. Human leukocyte antigen (HLA)-G and HLA-E are expressed on invasive trophoblast cells, and are supposed to confer to materno-fetal tolerance. A total of 14 different nucleotide sequences have been described for HLA-G, including one dysfunctional null allele (HLA-G*0105N), while five different sequences have been described for HLA-E. In this study, 78 RSA couples and 52 fertile controls were typed for HLA-G an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 34 publications
4
133
2
1
Order By: Relevance
“…Some previous studies were conducted to evaluate the significance of HLA-E alleles in the RM, and reported non-significant associations in contrary to the results of the present study [18][19][20]. However, the work of Tripathi et al [10] on Indians revealed higher frequency of HLA-E*0101 compared with HLA-E*0103, and the difference was significant (P = 0.043).…”
Section: Hla-e Genotypescontrasting
confidence: 94%
See 2 more Smart Citations
“…Some previous studies were conducted to evaluate the significance of HLA-E alleles in the RM, and reported non-significant associations in contrary to the results of the present study [18][19][20]. However, the work of Tripathi et al [10] on Indians revealed higher frequency of HLA-E*0101 compared with HLA-E*0103, and the difference was significant (P = 0.043).…”
Section: Hla-e Genotypescontrasting
confidence: 94%
“…It was reported that HLA-E*0101 allele is undetectable on HLA-E*0101 cell surface [19,20] and deficient expression of this allele at the foetomaternal interface specially when present in homozygous state as shown in this study may result in maternal NK cell activation, causing RM. The presence of higher frequency of HLA-E*0103 allele and HLA-E*0103 homozygous genotypes in control than in patients with RM may support the hypothesis that increases in level of expression of HLA-E*0103 provide better inhibition of NK cells and allow pregnancy maintenance in fertile controls.…”
Section: Hla-e Genotypesmentioning
confidence: 57%
See 1 more Smart Citation
“…The gene encoding the human leukocyte antigen-G (HLA-G), an important component of alloimmune recognition at the maternal -fetal interface, has been extensively studied. The presence of a null allele for the most common HLA-G isoform as well as distinct polymorphisms in the HLA-G promoter region, have been associated with recurrent miscarriage, suggesting that a functional protein is necessary for reproduction (Aldrich et al 2001;Pfeiffer et al 2001). Polymorphisms in genes including p53, p72, leukemia inhibiting factor (LIF), FAS-L, and the vascular endothelial growth factor (VEGF) gene have also been linked to increased rates of implantation failure and are undergoing investigation to determine their potential roles in women with RPL (Dumont et al 2003;Steck et al 2004;Brooks et al 2007;Hu et al 2007;Goodman et al 2008;Banzato et al 2013;Fraga et al 2014).…”
Section: Single Gene Defectsmentioning
confidence: 99%
“…As these observations were made in placentae obtained at delivery, it is not certain whether this alteration in expression is a consequence of other placental changes occurring during the course of this disorder or whether it is a key initiating lesion. In addition, a number of HLA-G polymorphisms, many of which appear to affect expression levels, have been associated with the incidence of RFL [33,[44][45][46][47].…”
Section: Preeclampsia: An Immune Disorder?mentioning
confidence: 99%